Stress and Its Impact on Employee Performance - Iskamto, Dedi (IJOSMAS, 2021)
The purpose of this study was to determine The Effect of Job Stress on Employee Performance. The research uses quantitative methods. For data analysis and hypothesis testing, SPSS version 26 is used. The test results show that work stress has a significant and negative effect on employee performance. Based on the coefficient of determination test (R2), the contribution of work stress to employee work performance is 0.783, or 78.3%, the rest is explained by other variables that do not exist in this study.